Teologia spisku: drobna przyjemność w grze suwerennością - Rafolt, Leo (Przekłady Literatur Słowiańskich, 2017)
Tłumaczenie z języka chorwackiego Barbara Rzeźniczak Redakcja tłumaczenia Katarzyna Majdzik i Leszek Małczak Theology of Conspiracy: Small Pleasure in the Play of Sovereignty The conspiracy mission of Marin Držić is being analysed in the context of sovereignty and political state of exception, from Schmitt to Agamben, as well as in the light of recent historical interpretations, from Jeličić and Pupačić to Tatarin and Kunčević. Držić’s letters to Cosimo I. and Francesco Medici are thus situated in the context of renaissance diplomatic thought. Based on some possibilities in their Croatian stylizations (Čale vs. Batistić), their political and theological semantics is revised. Keywords: conspiracy, sovereignty, political correspondence, exception